Services interfaces for interoperability of signaling computer interlocking on borders - Abourahim Ikram; Mohsine Eleuldj; Mustapha Amghar (Institute of Advanced Engineering and Science, 2023)
Technological developments in the field of railway signaling have allowed more and more flexibility in the management of rail traffic, especially with computer interlocking. However, differences in signaling principles from one country to another as well as differences in the structure of interlocking software and communication protocols depending on suppliers lead to interoperability difficulties at the borders between computer interlocking. Some deployed projects deal with interoperability issues regarding the communication of signaling information between the train and interlocking like the European rail traffic management system (ERTMS) project. Unfortunately, the interoperability between interlocking themselves is still not achieved. Some deployed projects deal with interoperability issues regarding the communication of signaling information between the train and interlocking like the ERTMS project. Unfortunately, the interoperability between interlocking themselves is still not achieved. This article draws up a proposed model for interfacing at the interlocking boundaries based on service-oriented architecture (SOA). In addition, to ensure the coupling of SOA services to the internal functions of the signaling computer interlocking, a distributed architecture of programmable logic controller according to the IEC 61499 standard is suggested.